Study of aero-engine oil-air separators - Wang, Y.; Simmons, K.; Eastwick, Carol; Hibberd, S. (SAGE, 2006)
For aero-engines, oil-air separation is a key function, and one approach to assessing separator effectiveness is computational fluid dynamics (CFD). The two-phase flow is complex and oil can be present in different forms (for example, droplets, mist, film). However, necessary modelling simplifications may affect solution accuracy and range of validity. This article presents a modelling methodology for oil-air separators; the effect of simplifications is discussed and their relative magnitude assessed. Comparison with available experimental data is presented. It is concluded that although simplification has an impact, the significant features of the oil-air separator are predicted with sufficient accuracy to allow design comparisons. Two separator configurations, one internal to a bearing chamber and one external, are modelled and the data presented. Flow fields are compared and the effectiveness of the separators in removing oil droplets prior to impact on the breather (primary separation) presented. The separation performance of the external design is largely independent of shaft speed, with all droplets >3 μm removed before impact on the breather. The critical droplet diameter of the internal design is larger, varying with breather configuration and shaft speed but the power loss is an order of magnitude lower than for the external design.